2021
DOI: 10.1080/23570008.2021.1941691
|View full text |Cite
|
Sign up to set email alerts
|

Delineation and mapping of palaeochannels using remote sensing, geophysical, and sedimentological techniques: A comprehensive approach

Abstract: Palaeochannels are remnants of rivers or stream channels that flowed in the past and have been currently filled or buried by younger fluviatile sediments. There are a number of techniques for detecting palaeochannels with each of them having its own intrinsic advantages and disadvantages. In the present study, apart from applying different approaches, the capabilities, and effectiveness of the approaches to locate and map palaeochannels are compared. Remote sensing-based approaches are comprised of high-resolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…An analysis of the landform digitally using the Alos Palsar DEM comparison with the vegetation index from Sentinel 2B imagery with a spatial resolution of 10 m [18]. This research is interpreted visually so that the interpretation is by the actual condition of the land cover object and topography [24]. The landform that spans the area is a volcanic downslope covering 11,578.95 ha (28.85%) of the total area of the study site.…”
Section: Factors Causing Landslide Susceptibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the landform digitally using the Alos Palsar DEM comparison with the vegetation index from Sentinel 2B imagery with a spatial resolution of 10 m [18]. This research is interpreted visually so that the interpretation is by the actual condition of the land cover object and topography [24]. The landform that spans the area is a volcanic downslope covering 11,578.95 ha (28.85%) of the total area of the study site.…”
Section: Factors Causing Landslide Susceptibilitymentioning
confidence: 99%
“…Based on the results of the extraction of the Digital Terrain Model of Alos Palsar Acquisition in 2011, the study area is classified into five classes of the slope, which are presented in fig 2e. Also, Palsar DEM is good for use in slope analysis because the height value in Alos Palsar DEM is the actual topographical height of the soil [24] without a canopy on it ( Digital Terrain Model ). The slope class with the 15-30% category dominates the research area covering an area of 9,119.38 ha (22.73%).…”
Section: Factors Causing Landslide Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several GPR profiles taken on the levee foot correspond with Ritambhara et al (2021) revealed the presence of paleo-river channels, and a unique reflector feature explained the old banks and the younger sediments that filled these channels. Because it might result in the growth of sand boils on the levee's protected side, , thus increasing flood risk (Nagy, 2000;Ojha et al, 2001;Tímár, 2020).…”
Section: Evaluation Of Levee Defectsmentioning
confidence: 96%